Effect of Pneumococcal Conjugate Vaccine on Pneumonia Incidence Rates among Children 2–59 Months of Age, Mongolia, 2015–2021 - von Mollendorf, Claire; Ulziibayar, Munkhchuluun; Nguyen, Cattram D.; Batsaikhan, Purevsuren; Suuri, Bujinlkham; Luvsantseren, Dashtseren; Narangerel, Dorj; de Campo, John; de Campo, Margaret; Tsolmon, Bilegtsaikhan; Demberelsuren, Sodbayar; Dunne, Eileen M.; et al. (Emerging infectious diseases, 2024)
Starting in June 2016, the 13-valent pneumococcal conjugate vaccine (PCV13) was introduced into the routine immunization program of Mongolia by using a 2+1 dosing schedule, phased by district. We used prospective hospital surveillance to evaluate the vaccine's effect on pneumonia incidence rates among children 2-59 months of age over a 6-year period. Of 17,607 children with pneumonia, overall adjusted incidence rate ratios showed decreased primary endpoint pneumonia, very severe pneumonia, and probable pneumococcal pneumonia until June 2021. Results excluding and including the COVID-19 pandemic period were similar. Pneumonia declined in 3 districts that introduced PCV13 with catch-up campaigns but not in the 1 district that did not. After PCV13 introduction, vaccine-type pneumococcal carriage prevalence decreased by 44% and nonvaccine-type carriage increased by 49%. After PCV13 introduction in Mongolia, the incidence of more specific pneumonia endpoints declined in children 2-59 months of age; additional benefits were conferred by catch-up campaigns.